Psychotherapy for depression among advanced, incurable cancer patients: A systematic review and meta-analysis. (May 2017) - Okuyama, Toru; Akechi, Tatsuo; Mackenzie, Lisa; Furukawa, Toshi A.
Highlights: Effectiveness of psychotherapy for depression in advanced cancer patients was tested. The result of meta-analysis indicated that psychotherapy was moderately effective. Few studies focused on people with clinically diagnosed depression. Abstract: Background: There is a high prevalence of depressive disorder and depressive symptoms among advanced, incurable cancer patients. Patients commonly report a preference for non-pharmacological treatments such as psychotherapy over pharmacological treatments for depression. The objective of this review was to investigate the effectiveness of psychotherapy for the treatment of depression in people with advanced, incurable cancer via a meta-analysis of randomized controlled trials (RCTs). Methods: We searched research databases and clinical trial registries for studies published prior to June 2015. No language restrictions were applied when selecting studies. Cochrane Collaboration meta-analysis review methodology was used. All relevant RCTs comparing psychotherapy with control conditions on depression outcomes for adults with advanced cancer were eligible for inclusion. We calculated pooled effect sizes using Hedges g and a standardized mean difference (SMD) of change between baseline and post-treatment scores. Quality of evidence was rated using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Results: Of 13 studies included in the review, 12 reported data suitable for meta-analysis. Psychotherapy was associated with moderate decrease in depression score (SMD −0.67, 95% confidence interval −1.06 to −0.29, P  = 0.0005). Few studies focused on people with clinically diagnosed depression. Overall, quality of evidence across the included studies was rated as low, and heterogeneity was high. Conclusions: Low quality evidence suggests that psychotherapy is moderately more effective for the amelioration of symptoms of depression among advanced, incurable cancer patients than the control conditions. There is insufficient high-quality evidence supporting the effectiveness of psychotherapy for patients with clinically diagnosed depression.